FIRM SIZE AND PROFITABILITY AFFECT TO DIVIDEND POLICY ON MINING COMPANIES LISTED IN INDONESIAN STOCK EXCHANGE PERIOD 2016-2020 - W Novianti (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research aims to investigate the influence of Firm Size and Profitability on the Dividend Policy of mining companies listed in the Indonesian Stock Exchange Period 2016-2020. The analysis method used descriptive and verification. The sample used was the company's financial statements totaling 15 pooled data. Statistical analysis used multiple linear regression analysis, correlation, determination coefficient and t test. The results of data processing obtained partially, Firm Size has an effect on Dividend Policy and Profitability has an effect on Dividend Policy.